Analysis of the Accuracy of Calculation of Production Costs and Cost of Products for Micro Businesses in the Food & Beverage Sector - Rachman, Yoga Tantular; Dianita, Mirna; Hadian, Niki; Tresnawati, Rina; Prayitno, Yogo Heru (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research provides an overview of the cost of a product for a business which is one of the main things and affects the business plan in the long term. Many of them determine the cost of a product only based on a rough estimate without clarity on the basic elements in the calculation of production costs such as direct labor costs and overhead costs. The research method is descriptive using literature studies and field surveys. The results of this study seek to help micro businesses engaged in the food & beverage sector calculate production costs and cost of products through a simple but more accurate calculation formula than what they have calculated so far. The managerial implication that can be done is that micro industries can apply cost of goods calculations more accurately.